The Influence of Instructional Models and Innovation Ability on Learning Outcomes of Alternative Energy Courses - ., Soeprijanto; Hanifati, Sarah Najla; ., Daryanto; ., Jarudin (International Journal of Membrane Science and Technology, 2023)
This study aims to examine and test the use of appropriate instructional models in teaching and learning activities of alternative energy courses by considering students’ innovation abilities to improve students’ cognitive learning outcomes. As a study of the effect of instructional models, this study aims to help teachers manage student instructional models. This research is quasi-experimental research with a 2x2 factorial design. This study used two classes, namely the Problem-Based Learning (PBL) instructional model class and the Student Team Achievement Division (STAD) instructional model class, with the characteristics of students who have high and low innovation abilities. This study used a sample of 22 students with 12 PBL groups and 10 STAD groups. The data analysis technique used ANOVA. The results showed that: (1) there is no significant difference between learning outcomes with learning models. (2) there is an interaction between the instructional model and innovation ability, (3) there is no significant difference between PBL and STAD learning outcomes in students with innovation ability.